(untitled) (Euro-Latin American Journal of Administrative Law, 2025)
This study, analyzing the intersection of trade and socio-environmental governance, investigates how the requirement for environmental, social, and governance (ESG) criteria influences business practices beyond the borders of the European Union (EU). The research adopts a qualitative methodology based on documentary analysis and case studies of large European companies that already publish sustainability reports aligned with the Corporate Sustainability Reporting Directive (EU) 2022/2464 (CSRD) and international standards. The results demonstrate that the EU exerts indirect regulatory pressure on third-country companies integrated into its value chains, encouraging the adoption of standardized reports and reinforcing the role of transnational administrative governance in promoting sustainability. The analysis also indicates that large companies in the Southern Common Market (MERCOSUR) are progressively converging on these standards, demonstrating alignment with EU standards and opening up prospects for regulatory harmonization within the Agreement. This dynamic creates both opportunities and challenges: although standardization promotes innovation and transparency, it imposes significant compliance costs, especially for small and medium-sized companies within MERCOSUR. It is concluded that international trade agreements can act as instruments of global sustainability governance, provided they are designed to balance competitiveness and socio-environmental protection through specific provisions, monitoring and technical cooperation, thus strengthening the role of governments and companies in this process.